Intestinal tumorigenesis initiated by dedifferentiation and acquisition of stem-cell-like properties - Schwitalla, Sarah; Fingerle, Alexander A.; Cammareri, Patrizia; Nebelsiek, Tim; Goektuna, Serkan I.; Ziegler, Paul K.; Canli, Ozge; Heijmans, Jarom; Huels, David J.; Moreaux, Guenievre; Rupec, Rudolf A.; Gerhard, Markus; et al. (Cell, 2013)
Cell-type plasticity within a tumor has recently been suggested to cause a bidirectional conversion between tumor-initiating stem cells and nonstem cells triggered by an inflammatory stroma. NF-κB represents a key transcription factor within the inflammatory tumor microenvironment. However, NF-κB's function in tumor-initiating cells has not been examined yet. Using a genetic model of intestinal epithelial cell (IEC)-restricted constitutive Wnt-activation, which comprises the most common event in the initiation of colon cancer, we demonstrate that NF-κB modulates Wnt signaling and show that IEC-specific ablation of RelA/p65 retards crypt stem cell expansion. In contrast, elevated NF-κB signaling enhances Wnt activation and induces dedifferentiation of nonstem cells that acquire tumor-initiating capacity. Thus, our data support the concept of bidirectional conversion and highlight the importance of inflammatory signaling for dedifferentiation and generation of tumor-initiating cells in vivo.
EVALuna2:7625